The study on store loyalty at Aeon Seberang Perai City grocery department / Azrul Kamal Ramli - Ramli, Azrul Kamal (2013)
Modem retailers such as hypermarket need to be more customer-oriented in order to survive in today's competitive business world. In this study, researcher will find out the relationship between store satisfaction, product quality, service quality and store loyalty. AEON Seberang Prai City Shopping Centre customer will be the respondent for this study. The research model adapted from N.R.V. Ramana Reddy, T.N. Reddy and Abdul Azeem (2010) in this research to link store satisfaction, merchandise quality and service quality with store loyalty. Three hypothesis have been formulated to examine the relationship proposed. 120 sets of questionnaire were distributed to respondent but only 105 sets were return. The collected data have been analyses with statistical program SPSS 17 to produced Frequency distribution, Descriptive, Reliability, Pearson correlation and Multiple regression. The Finding of the study show that only store satisfaction have significant influence on store loyalty.